Customer service in supply chain management: a case study. Issue 6 (23rd August 2014) - Naoui, Fatiha
Abstract : Purpose: The purpose of this paper is to present a case study to assess the customer service within supply chain management (SCM). In particular, the paper emphasizes an interest in an integrated approach to considering customer service performance in an efficient way. Indeed, information systems as technical support play an essential role in the SCM of small and medium-sized enterprises. The reasons for pursuing such research can be explained by the fact that the customers are the first concern of any firm that seeks to be competitive. Indeed, we seek to answer the following question: Which are the main explaining factors of the customers' service performance within Alpha SCM? Design/methodology/approach: A qualitative research methodology is used based on 11 semi-structured interviews with professionals and direct observation as part of a telecommunications network SME in France. Findings: This empirical case study is to delineate the concept dimensions. These dimensions allow the drawing up of a framework of actions to improve SME customer service performance evaluations in the supply chain management. Research limitations/implications: The paper is a single case study, not generalisable, but might be useful in general way. Another issue that we can reflect on is the KPIs. The KPIs selected are rather subjective and not generic relating to supply chain as "process". The answers correspond to the managers' perception and the international dimension is not taken into account in this work. Practical implications: The results contribute to the existing body of knowledge regarding services for improving the relationship with the customers; improve operational reporting; improve invoice control and indicator follow-ups with the Project Manager; and improve cost management. Originality/value: The paper adds to our understanding by showing that the human motivation and intellectual capital management are critical success factors in the Alpha SCM case study. It offers a new perspective that customers are among the major actors in the telecommunications market, along with the corporate customers and administration involved in implementation or service quality follow-up and telecommunications use. The group offers a wide range of skills to help the customers to make the most of technology.